Covid-19 and its impact on migration in Malaysia - Borhan Abdullah; Rosli Sareya; Andi Tamsang Andi Kele; Rostika P. Boroh; Shafinaz Naim (Universiti Malaysia Sabah, 2021)
The COVID-19 pandemic has affected countries all over the world. Many countries have imposed restrictive measures, such as lockdowns, shelter-in-place, and stay-at-home orders, as an attempt to control the pandemic at a local level. However, these measures also hit hard the economy. This paper predicts the impact of COVID-19 on migration in Malaysia based on the experience during the Asian financial crisis. Migrant workers contribute large portion in the labour market in Malaysia. Thousands of migrant workers especially the unskilled workers are predicted to be unemployed due to the COVID-19 and the implementation and re-imposition of multiple phases of Movement Control Order (MCO) worsened the economy. Therefore, there is a need to review the possible effect of COVID-19 on migration as it would greatly affect the labour market and the economy as a whole.